The Fermentation Process Improves the Nutritional Value of Rapeseed Cake for Turkeys—Effects on Performance, Gut Bacterial Population and Its Fermentative Activity - Aleksandra Alicja Drażbo; Jerzy Juśkiewicz; Agata Józefiak; Paweł Konieczka (Animals, 2020)
This experiment investigated the potential inclusion of fermented rapeseed cake (FRC) in turkey diets. The turkeys received diets either not supplemented (C) or supplemented with raw rapeseed cake (RRC) or FRC at 150 g/kg diet. In comparison with RRC, turkeys receiving FRC achieved significantly higher final BW comparable with that noted in the control group. The dietary inclusion of FRC increased the concentrations of propionic and valeric acid in the cecal digesta compared with the control group, and increased the proportion of butyric acid in SCFA profile compared with RRC group. The activities of glycolytic bacterial enzymes in the cecal digesta, were lowest in turkeys fed FRC. Experimental diets did not cause a shift in the relative abundances of the main bacterial phyla or orders in the cecal digesta. FRC increased the abundance of Bacteroidaceae at the family level, but decreased the abundance of Lactobacillus at the genus level compared with birds fed RRC. In conclusion, the dietary inclusion of FRC at 150 g/kg did not compromise bird performance, did not excessively stimulate bacterial activity, and did not cause shifts in the bacterial composition in the cecum. Actually, FCR exerted several beneficial effects that contributed to maintaining gut health in turkeys, which points to its advantage over RRC.